1976
DOI: 10.1073/pnas.73.9.3126
|View full text |Cite
|
Sign up to set email alerts
|

The identification of the mot gene product with Escherichia coli-lambda hybrids.

Abstract: Molecular cloning techniques were used to construct lambda-E. coli hybrid bacteriophage carrying genes involved in bacterial flagellar motility (mot) and chemotaxis (cheA). A series of hybrid bacteriophage without each of these genes was also prepared. When paralyzed mutants of E. coli were infected with lambda that carried the mot gene, the ability of the bacterium to swim was rapidly restored. The restoration of motility was the result of the synthesis and insertion into the cell membrane of a protein with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…Loss-of-function mutations in only two genes (motA and motB) yield the Mot phenotype, which is a flagellated but paralyzed cell. Insertion of the torque-generating components of the motor into the membrane is not required for assembly of the E. coli flagellar organelle, and expression of mot genes occurs at the final stage in the hierarchy of expression (57). The phenotypes of V. parahaemolyticus motility mutants differed from E. coli.…”
Section: Resultsmentioning
confidence: 86%
“…Loss-of-function mutations in only two genes (motA and motB) yield the Mot phenotype, which is a flagellated but paralyzed cell. Insertion of the torque-generating components of the motor into the membrane is not required for assembly of the E. coli flagellar organelle, and expression of mot genes occurs at the final stage in the hierarchy of expression (57). The phenotypes of V. parahaemolyticus motility mutants differed from E. coli.…”
Section: Resultsmentioning
confidence: 86%
“…The predatory lifecycle of B. bacteriovorus revolves around its ability to swim. In E. coli or Salmonella typhimurium, disruption of the motA or motB gene results in paralysis of bacterial motility despite the presence of an intact flagellum (Blair & Berg, 1988;Silverman et al, 1976). The MotA and MotB proteins constitute the stationary part of the flagellar motor (Chun & Parkinson, 1988;De Mot & Vanderleyden, 1994;Garza et al, 1995) and form a complex that facilitates the traffic of protons from the periplasmic space into the cytosol of the bacterial cell (Blair & Berg, 1990;Braun et al, 1999;Stolz & Berg, 1991;Zhou et al, 1998), which is required for flagellar rotation (Manson et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For a review see, for example, reference 14. What is actually known of the cellular location of the Mot proteins? They are normally present in amounts too low to be detected biochemically, but programmed expression of the genes cloned onto lambda hybrid phage (19) enabled the motA and motB gene products to be identified (as proteins with apparent molecular masses of 31 and 39 kilodaltons [kDa], respectively) and indicated that they are located in the cytoplasmic membrane (17), a location consistent with their function; a membrane location was also noted subsequently with plasmid-encoded MotA (22) and MotB (6).…”
mentioning
confidence: 99%